A snapshot on composition and distribution of fish larvae across the North Atlantic Ocean - Mohd Nasarudin, Harith; Cieran, O'Donnell; Graham, Johnston; Anne Marie, Power (Society for Indonesian Biodiversity, 2021)
Harith MN, O’ Donnell C, Johnston G, Power AM. 2021. A snapshot on composition and distribution of fish larvae across the North Atlantic Ocean. Biodiversitas 22: 4496-4504. This study aims to describe the composition and distribution patterns of fish larvae communities across the North Atlantic Ocean. Several cruises were involved in the effort to collect the fish larvae samples. The sampling took place on the east side of the North Atlantic Ocean, towards the mid-Atlantic Ocean, and on the west side of the North Atlantic Ocean, near the eddies approaching Flemish Cap. A total of 9522 fish larvae were collected and identified from these surveys. These larvae came from 79 taxa and 29 families. Referring to the total abundance, considering all the sampled stations, Atlantic mackerel (Scomber scombrus) was the most abundant species (38.82% of the total fish larvae abundance), followed by blue whiting (Micromesistius poutassou) (15.9%). Referring to the Multi-dimensional scaling (MDS) ordination plots, two major stations clusters separate the on-shelf and off-shelf stations supported by SIMPER analysis. This study provides a snapshot of larval fish concentrations and assembly structure, but current knowledge suggests that the distribution of larval fish assemblages will be highly spatially variable, more research into plume front dynamics and their effects on the region's biota is needed to predict and understand changes.